2019
DOI: 10.3889/oamjms.2019.668
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Removable Partial Denture Type on Patient Satisfaction and Abutment Survival Rate-RCT

Abstract: BACKGROUND:Patient’s satisfaction and the preservation of abutments is the most important outcomes that the clinician seeks during fabrication of any dental treatment, especially when it is concerned with removable prosthodontic rehabilitation.AIM:The present study evaluates three different Removable Partial Denture (RPD) types restoring mandibular class II modification I edentulous cases with regards to patient’s satisfaction and abutments survival.METHODS:Forty-two partially edentulous patients were divided … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…Material used in removable prosthesis fabrication also have an impact on the patient sastisfaction which was reported in a study done by Sherif A. Sadek and Dina Elawady[ 16 ] in which they concluded that patient satisfaction was improved with thermopress removable prosthesis as compared with vitallium removable prosthesis. In one of the clinical trials done by Fueki K[ 17 ] et al reported that patient satisfaction was higher when the removable prosthesis was fabricated with thermoplastic resin as compared with metal clasp retained removable prosthesis.…”
Section: Discussionmentioning
confidence: 96%
“…Material used in removable prosthesis fabrication also have an impact on the patient sastisfaction which was reported in a study done by Sherif A. Sadek and Dina Elawady[ 16 ] in which they concluded that patient satisfaction was improved with thermopress removable prosthesis as compared with vitallium removable prosthesis. In one of the clinical trials done by Fueki K[ 17 ] et al reported that patient satisfaction was higher when the removable prosthesis was fabricated with thermoplastic resin as compared with metal clasp retained removable prosthesis.…”
Section: Discussionmentioning
confidence: 96%
“…Abutment teeth were peri-apically radiographed to notice any carious lesions, assess pulp size, inspect length, size, shape, number and inclination of roots. Moreover, this played role in assessing abutment's supporting structure, investigating lamina dura's continuity, periodontal space's width, crown/root ratio and detecting of any periapical or periodontal lesions (5).…”
Section: Discussionmentioning
confidence: 99%
“…Considerable variations exist in removable partial denture design, materials (acrylic vs. cobalt‐chrome), span and indication. Data from the literature would indicate that the survival rate of abutment teeth supporting the denture has been reported in the literature to be from 7.5% to 15% per year 22–24 . Estimates of the necessary sample size were based on Hsieh and collaborators 25 and Bujang and collaborators 26 recommendations for minimum sample size to conduct a multiple logistic regression analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Data from the literature would indicate that the survival rate of abutment teeth supporting the denture has been reported in the literature to be from 7.5% to 15% per year. [22][23][24] Estimates of the necessary sample size were based on Hsieh and collaborators 25 and Bujang and collaborators 26 recommendations for minimum sample size to conduct a multiple logistic regression analysis. Using a survival rate of 15%, as a proxy to the need to include additional teeth in removable partial dentures, [22][23][24] some 534 are required to perform a multiple logistic regression analysis yielding a power of 0.80, at a two-sided significance level of 0.05, using up to 8 independent variables.…”
Section: Sample Sizementioning
confidence: 99%
See 1 more Smart Citation